Peningkatan Kinerja Ukm Dengan Pengelolaan Intellectual Capital Dan Inovasi - Maya Indriastuti; Dista Amalia Arifah (Conference In Business, Accounting, And Management (CBAM), 2012)
SMEs played important role in supporting national economic also created new work field and improved public prosperity. For rising SMEs performance they had to maximize their Intellectual Capital and Innovation. However, only little SMEs Adopted Intellectual Capital and innovation for rising their performance.This study aims to analyze the influence of intellectual capital and inovation on SMEs performance. The population used SMEs in handycraft cluster at Semarang city. Sampling using a purposive sampling method and obtained 80 responden as sample. Primary data was used in this research by distribute questioner and processed by multiple regression. The results showed that Intellectual Capital variable which are Structure Capital and Relational Capital influenced SMEs performance, analysis revealed less than 5% of level significant. Whereas innovation variable were insignificant affected SMEs performance.Keywords : Intellectual Capital, Innovation, SMEs, Companies Performance